Local Tourists' Assessment of the Elements of Tourism Development in Medan - Fauzia Agustini; Dita Amanah; Dedy Ansari Harahap (Universitas Pendidikan Indonesia, 2022)
A b s t r a c tThis study was to analyzed the assessment of local tourists on the elements of tourism development in Medan. This research is descriptive research with the sampling technique used Accidental Sampling. Samples were 354 respondents who are the community of Medan City. Data were collected through literature study and questionnaire distribution. The results which are categorized as the best three are the development of hotels in the city of Medan, the ease of use of public transportation and the condition of electricity. On the other hand, the results of the assessment of the three worst categories are road conditions, traffic, and cleanliness of the city. The community and the Medan city government must care and work together in advancing the tourism sector in the city that the city of Medan is expected to get the nickname of the city of Paris van Sumatra.A b s t r a kPenelitian ini bertujuan untuk menganalisis penilaian wisatawan lokal terhadap unsur-unsur pengembangan pariwisata di Kota Medan. Penelitian ini merupakan penelitian deskriptif dengan teknik pengambilan sampel menggunakan Accidental Sampling. Sampel sebanyak 354 responden yang merupakan masyarakat Kota Medan. Pengumpulan data dilakukan melalui studi kepustakaan dan penyebaran kuesioner. Hasil yang masuk dalam kategori tiga terbaik adalah perkembangan hotel di kota Medan, kemudahan penggunaan transportasi umum dan kondisi kelistrikan. Sedangkan hasil penilaian dari tiga kategori terburuk adalah kondisi jalan, lalu lintas, dan kebersihan kota. Masyarakat dan pemerintah kota Medan harus peduli dan bersinergi dalam memajukan sektor pariwisata di kota sehingga kota Medan diharapkan mendapat julukan kota Paris van Sumatra.